Adherence to a lifestyle program for youth with type 2 diabetes and its association with treatment outcome in the TODAY clinical trial. Issue 2 (30th June 2017) - Berkowitz, Robert I; Marcus, Marsha D; Anderson, Barbara J; Delahanty, Linda; Grover, Nisha; Kriska, Andrea; Laffel, Lori; Syme, Amy; Venditti, Elizabeth; Van Buren, Dorothy J; Wilfley, Denise E; Yasuda, Patrice; et al.
Abstract : Objective: To assess the association of proxies of behavioral adherence to the Treatment Options for type 2 Diabetes in Adolescents and Youth (TODAY) lifestyle program with changes in glycemic control and obesity in a multi‐ethnic sample of youth with type 2 diabetes. Methods: The TODAY clinical trial included an intensive lifestyle intervention to promote weight reduction. Adherence was assessed with measures of attendance at intervention sessions and rates of self‐monitoring of diet and physical activity by participants and their caregivers. The relation between participant characteristics and consistency of proxies of adherence were examined across 3 phases of intervention. Results: A total of 234 TODAY youth were randomized to the lifestyle program. Overall rate of session attendance was approximately 60% of planned sessions. Participants with an adequate dose of session attendance (≥75% attended) did not differ from those who attended <75% of sessions in glycemic control, but did have significantly greater reductions in percent overweight compared with those who attended fewer than 75% of sessions. Rates of self‐monitoring were low and additional analysis was not possible. Conclusions: Rates of session attendance were moderate in a lifestyle program for youth with type 2 diabetes, but levels of self‐monitoring, considered a key lifestyle change behavior, were low. Glycemic control was not significantly associated with session attendance but reductions in percent overweight were. Given the salience of program attendance and self‐monitoring to lifestyle weight management established in other populations, future research is needed to understand, develop, and promote strategies and interventions targeting weight loss to achieve improved glycemic control in youth diagnosed with type 2 diabetes.